The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/bjs.10980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy for rectal cancer on ovarian androgen production

Abstract: Background The impact of radiotherapy (RT) for rectal cancer on ovarian androgen production is unknown. The aim was to examine the effect of RT for rectal cancer on androgen levels in non‐oophorectomized women and the association with female sexual desire. Methods This prospective cohort study included women who had surgery for rectal cancer with or without RT. Serum testosterone, free testosterone, androstenedione and dehydroepiandrosterone sulphate (DHEA‐S) levels were assessed at baseline, after RT and 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A reduction of sexual desire has recently been described as a result of impaired androgen production from the ovaries. 210 Other long-term side effects of RT are pelvic insufficiency fractures (PIF), with chronic pelvic pain as cardinal symptom. A Danish case-control study found that 12.2 % of 1100 patients had PIF after CRT during a follow up of 36 months.…”
Section: Toxicity From Radiotherapymentioning
confidence: 99%
“…A reduction of sexual desire has recently been described as a result of impaired androgen production from the ovaries. 210 Other long-term side effects of RT are pelvic insufficiency fractures (PIF), with chronic pelvic pain as cardinal symptom. A Danish case-control study found that 12.2 % of 1100 patients had PIF after CRT during a follow up of 36 months.…”
Section: Toxicity From Radiotherapymentioning
confidence: 99%
“…[1,2] Most patients with colorectal cancer have simultaneous peritoneal metastases. [3,4] Colorectal peritoneal carcinomatosis (CRPC) is the main reason for treatment failure. [5] Chemotherapy has been widely applied in conventional treatment of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of preoperative RT on sexuality could be explained by the fact that normal tissue within the irradiated area is damaged, which in turn may lead to vascular and genital tissue fibrosis, vaginal narrowing and loss of elasticity, pelvic pain and neurological damage. An additional factor contributing to sexual dysfunction could be RT‐induced impairment of ovarian androgen production. Apart from these physical effects, relationship factors are important for sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Details of this longitudinal cohort study have been described previously. Women with stage I–III rectal cancer were included prospectively between June 2008 and August 2013 from five Swedish referral centres for rectal cancer surgery (Karolinska University Hospital, Ersta Hospital, Örebro University Hospital, Linköping University Hospital and Norrköping Hospital).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation